Pengaruh Metode Tutor Sebaya Terhadap Hasil Belajar Peserta Didik Pada Materi FPB Di Kelas IV SDN 1 Mata Ie Aceh Besar - Rani Fathul Adawiyah; Linda Vitoria; Mislinawati Mislinawati (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
The whole big problem that exists in Indonesia, the most often discussed is the lack of quality education. This condition can occur because of the inefficient teaching and learning process in schools. To be able to study the learning process by students, educators need to understand the basic concepts of learning as stated in Constitution Number 20 of 2003 Article 1 paragraph 1 concerning the national education system. This research uses a quantitative approach with the type of experimental research one group pretest post-test design. The subjects of this study were fourth-grade students of SDN 1 Mata Ie Aceh Besar. The researcher's data collection technique used a test. Based on the results of the information, it can be seen that 1) the learning value of students with the peer tutor method is very influential. This was found by the researchers when giving test questions in the form of pretest and posttest. When the pretest questions were given, it was seen that only a few students had reached the KBM, while some of the others did not understand what FBP was. 2) After applying the peer tutoring method, the student's learning scores increased when they were given post-test questions. 3) when applying the peer tutoring method, students do not hesitate to ask their friends, and those who become tutors use language that is easily understood by their friends and students are able to answer the questions given. Thus, it is concluded that the peer tutoring method is one method that can improve student learning outcomes in the subject of FPB in grade IV SDN 1 Mata Ie Aceh Besar.